Piezoelectricity, acoustic waves and device applications : proceedings of the 2006 Symposium, Zhejiang University, China, 14-16, December 2006 - Symposium on Piezoelectricity, Acoustic Waves and Device Applications (2nd : 2006 : Zhejiang University, China); Wang, Ji; Chen, Weiqiu (Hackensack, NJ : World Scientific, 2007)
16